Fabrication of hollow boron-doped diamond nanostructure via electrochemical corrosion of a tungsten oxide template. (7th June 2018) - Lim, Young-Kyun; Lee, Eung-Seok; Lee, Choong-Hyun; Lim, Dae-Soon
Abstract: In the study, a hollow boron-doped diamond (BDD) nanostructure electrode is fabricated to increase the reactive surface area for electrochemical applications. Tungsten oxide nanorods are deposited on the silicon substrate as a template by the hot filament chemical vapor deposition (HFCVD) method. The template is coated with a 100 nm BDD layer deposited by HFCVD to form a core–shell nanostructure. The WO x core is finally electrochemically dissolved to form hollow BDD nanostructure. The fabricated hollow BDD nanostructure electrode is investigated via scanning electron microscopy, transmission electron microscopy, and Raman spectroscopy. The specific surface areas of the electrodes were analyzed and compared by using Brunauer–Emmett–Teller method. Furthermore, cyclic voltammetry and chronocoulometry are used to investigate the electrochemical characteristics and the reactive surface area of the as-prepared hollow BDD nanostructure electrode. A hollow BDD nanostructure electrode exhibits a reactive area that is 15 times that of a planar BDD thin electrode.